Juridical Implications of Making of the Deed of Binding the Sale and Purchase of Land that Guarantees Individual Debt - Pratiwi, Eka (Jurnal Konstatering, 2022)
As social beings, humans need other humans to meet their needs. What's more, the human need for land continues to increase, in line with the increasing human population in Indonesia. Fulfilling the need for the land, can be done by carrying out sale and purchase transactions, and transferring rights over the land in order to obtain valid legal certainty in accordance with applicable regulations. The more important the need for land, the more problems that arise related to the transfer of land rights. As with the buying and selling process in general, besides the subject and object that must be clear, in buying and selling land there will also be rights and obligations that must be fulfilled by both parties. If one party is negligent and does not fulfill its obligations, as stated in the agreement. As described above, the author is interested in conducting research with the title "Juridical Implications of Making Deeds of Sale and Purchase Binding of Land that Become Guarantees for Individual Debt". The formulation of the problem to be examined is (1) what are the juridical implications of making a Sale and Purchase Binding Deed for land objects that are collateral for individual debt, made by a Notary? (2) what is the position and responsibility of the parties to the Deed of the Sale and Purchase Agreement? (3) what is the form of the Deed of Sale and Purchase Agreement on the land that serves as collateral for individual debt? The research method used to obtain data in this study, uses a normative juridical approach, with descriptive research specifications analytical. This normative legal research is also referred to as library legal research, where library materials constitute basic data in (science) research which is classified as secondary data, and then analyzed qualitatively. Based on the results of research conducted by the author, it is known that the legal consequences of making the Deed of Agreement Binding Sale and Purchase Authorization, which is the object of sale and purchase in the agreement, is the object of collateral for the individual debt to be null and void. sale and purchase in the agreement, is the object of collateral for the individual debt to be null and void by law. The Buyer can apply for a return of payment for land, compensation or fines, due to non-fulfillment of the obligations of the Seller, as stated in the Sales and Purchase Agreement.Keywords: Guarantees; Implications; Juridical.